EFEKTIVITAS PENURUNAN KADAR DODESIL BENZEN SULFONAT (DBS) DARI LIMBAH DETERJEN YANG DIOLAH DENGAN LUMPUR AKTIF - Dwi Adhi Suastuti, Ni G. A. M. (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 1 Januari 2010)
This research aims to find out the decrease effectivity of dodecil benzene suphonate (DBS) concentration from detergent waste treated using activated sludge. This research was carried out in two steps : the first step was seeding process or preparation of the activated sludge. This was carried out on plastic container of 2 L. About 3 g sediment taken from Tukad Mati, 1 g NPK were mixed in a plastic container. The volume was made 1 L by adding aquadest, the mixture was aerated for 1 week. The second step was treatment of detergent waste which was carried out using 2 plastic container of 5 L each. About 2 L detergent waste and 1 L activated sludge solution were mixed in the plastic container. Mean while, 3 L detergent waste as a control were palced in the other plastic container. Both container were aerated for observation for decrease DBS concentration was carried out during 0, 3, 5, 7, 10 and 15 days. DBS concentration was analyzed using Methylen blue method. The research result indicated that generally, there were decrease of BDS concentration both in control and treated samples. The lowest DBS concentration was observed on day 15 both on control and treated samples with value, of 46.726 and 0.381 mg/L respectively. The decrease effectivity were 8.18% for control and 99,25% for treated samples. From this research, it can be seen that treatment of waste using activated sludge was effective to decrease DBS concentration in detergent containing waste.
Keywords: activated sludge, DBS, detergent waste